Comparison of in Batch Aerobic and Anaerobic Processes for the Degradation of Organic Matter in a Tropical Reservoir - Rodríguez-Ballesteros, Johanna Elvira; Rodriguez-Loaiza, Diana Catalina; Peñuela-Mesa, Gustavo Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The decomposition of submerged organic matter after the flooding process of a reservoir and the organic matter transported by the tributaries that supply it, gives rise to the formation of greenhouse gases (GHG), such as CO2 and CH4, product of the aerobic and anaerobic biological processes that take place both on the surface and at the bottom of the reservoir. In this study, the dynamics of aerobic and anaerobic processes as well as the generation of greenhouse gases in the degradation of organic matter, present in a tropical reservoir, were compared. Batch reactors and plant material extracted from the protection strip were used. Likewise, the behavior of the variation of the COD, physicochemical parameters such as pH, dissolved oxygen, redox potential, and conductivity were evaluated, and the kinetic constants that represent the behavior of organic matter were defined. The results showed that the degradation of the organic material leads to the generation of GHG, however, when using water plus vegetal material, the GHG increased considerably after a time. This process is due to the fact that the plant material suffers the breakdown of its polymer chains and so it degrades more quickly, which increases the concentration of organic matter available to microorganisms. GHG values ​​were on average 10.290 g CO2eq/m2.d with water only, and 24.536 g CO2eq/m2.d with water and vegetal material for aerobic processes. In anaerobic processes, the values were on average 12.056 g CO2eq/m2.d with water only, and 33.470 g CO2eq/m2.d with water plus vegetal material. These laboratory scale results allow analyzing the behavior of the reservoir and the incidence of flooded plant material on GHGs.